Surgical outcome of prognostic factors for final outcome of hand function following primary median nerve repair - Dhanaraju, S.; Kannan, N. (International Surgery Journal, 2018)
Background: A major problem in surgery of median nerve injuries is the unpredictable final outcome, so identifying the prognostic factors for final outcome is needed in primary median nerve repair following injury. Assessing the functional recovery of hand function following median nerve repair. Methods: Total no. of patients with median nerve injury repaired in our institution was 70. All the patients assessed preoperatively by clinical examination, surgery performed immediately or within 12 hours of injury, performed under axillary block and tourniquet control, Multiple surgeons involved (about 6 surgeons). All are primarily repaired nerves, repair by 70 prolene epineural sutures, postoperative immobilization of 3 weeks. Results: Median nerve injury associated with other flexors involved patients show good functional recovery, the functional recovery deteriorate once involvement of finger flexors, particularly if all the tendons were injured. The arterial injury and repair don’t seem to influence the outcome of the hand function, but both artery involvement usually associated with all tendon injury, it shows poor outcome. Conclusions: The more distal the injury the outcome will be quicker as compared to middle 1/3 and proximal 1/3 injuries. Pure median nerve injuries sensory recovery in S4 grade about 5%, S3+ recovery of sensation is about 36%. Pure median nerve injury patients M4 motor recovery about 54%.Only median nerve injury the final outcome is good but combined median and ulnar nerve injury and associated tendon injury the outcome is poor.